2021
DOI: 10.1159/000513038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Key Distinct Biological Characteristics of Human Placenta-Derived Mesenchymal Stromal Cells and Individual Heterogeneity Attributing to Donors

Abstract: For potential clinical applications in the future, we investigated the distinct biological features of mesenchymal stromal cells (MSCs) derived from different origin areas of human placenta and individual heterogeneity among different donors. Chorionic plate MSCs (CP-MSCs), amniotic membrane MSCs (AM-MSCs), and decidual plate MSCs (DP-MSCs) were isolated from 5 human placentae and were analyzed in terms of main features of MSCs including surface marker profile, growth, differentiation potential, immune regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…They discovered only a moderate heterogeneity in osteogenic and adipogenic differentiation potentials in samples obtained from different placental regions in enrolled individuals. Similar heterogeneity was observed in the tubulin acetylation measured in different samples [ 216 ]. Moreover, they discovered that only the chorionic plate MSCs could decrease the proliferation of peripheral blood mononuclear cells (PBMCs) triggered by the phytohemagglutinin.…”
Section: Mesenchymal Stem/stromal Cells Derived From Human and Animal Perinatal Tissuessupporting
confidence: 78%
See 1 more Smart Citation
“…They discovered only a moderate heterogeneity in osteogenic and adipogenic differentiation potentials in samples obtained from different placental regions in enrolled individuals. Similar heterogeneity was observed in the tubulin acetylation measured in different samples [ 216 ]. Moreover, they discovered that only the chorionic plate MSCs could decrease the proliferation of peripheral blood mononuclear cells (PBMCs) triggered by the phytohemagglutinin.…”
Section: Mesenchymal Stem/stromal Cells Derived From Human and Animal Perinatal Tissuessupporting
confidence: 78%
“…Moreover, they discovered that only the chorionic plate MSCs could decrease the proliferation of peripheral blood mononuclear cells (PBMCs) triggered by the phytohemagglutinin. All cell lineages decreased the proportions of CD3+/CD8-/IFN-γ+ Th1 and CD3+/CD8-/IL17+ Th17 cells and elevated the proportion of Treg in PBMCs [ 216 ]. Placenta-derived MSCs regulate trophoblast functioning by promoting increased cell survival and protecting mitochondria from the effects of oxidative stress and, as a result, facilitate trophoblast invasion in humans [ 217 , 218 ].…”
Section: Mesenchymal Stem/stromal Cells Derived From Human and Animal Perinatal Tissuesmentioning
confidence: 99%
“…Even of MSCs are obtained from the same individual but at the different sampling location, the properties of the obtained MSCs may be different. A meaningful study confirmed it in 2021 [ 255 ]. In this work, they conducted a number of experiments to investigate the different biological characteristics and heterogeneity among different donors of chorionic plate mesenchymal stem cells (CP-MSCs), AMSCs, and decidual plate mesenchymal stem cells (DP-MSCs) isolated from human placenta.…”
Section: The Challenge Of Mscs For Senescence Therapy In Clinicmentioning
confidence: 71%
“… 107 In addition, MSCs derived from different donors and tissues lead to individual heterogeneity, which complicates the progress of consistent and standardized stem cell production. 108 , 109 Therefore, it is necessary to screen qualified MSCs to avoid uncertain effects.…”
Section: Challenges and Perspectivementioning
confidence: 99%